2024
DOI: 10.7150/thno.91814
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence and therapeutic implication of PANoptosis in cancer

Dickson Kofi Wiredu Ocansey,
Fei Qian,
Peipei Cai
et al.

Abstract: Regulated cell death (RCD) is considered a critical pathway in cancer therapy, contributing to eliminating cancer cells and influencing treatment outcomes. The application of RCD in cancer treatment is marked by its potential in targeted therapy and immunotherapy. As a type of RCD, PANoptosis has emerged as a unique form of programmed cell death (PCD) characterized by features of pyroptosis, apoptosis, and necroptosis but cannot be fully explained by any of these pathways alone. It is regulated by a multi-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Cancer cells exhibit a remarkable ability to evade the tightly regulated pathways of cellular death, a hallmark feature of their malignancy [115]. This evasion has posed a challenge within cancer therapies as the resistance of cancer cells to programmed cell death pathways diminishes treatment efficacy [116]. However, cuproptosis presents a potential opportunity for overcoming this resistance and promoting cell death in cancer cells.…”
Section: Elesclomol: An Anticancer Agentmentioning
confidence: 99%
“…Cancer cells exhibit a remarkable ability to evade the tightly regulated pathways of cellular death, a hallmark feature of their malignancy [115]. This evasion has posed a challenge within cancer therapies as the resistance of cancer cells to programmed cell death pathways diminishes treatment efficacy [116]. However, cuproptosis presents a potential opportunity for overcoming this resistance and promoting cell death in cancer cells.…”
Section: Elesclomol: An Anticancer Agentmentioning
confidence: 99%
“…This process is crucial for maintaining the body’s balance and defending against diseases by removing harmful cells ( 5 ). Intriguingly, PANoptosis has been implicated in the progression of various diseases, including cancer, highlighting its potential as a target for innovative treatments ( 6 ). For example, research has indicated that manipulating PANoptosis pathways could influence the development of tumors and the effectiveness of cancer therapies ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, targeting these cell death pathways have shown promising effects in cancer treatment ( 24 26 ). Although there are studies demonstrating that identifying PANoptosis patterns in cancer can predict survival and response to immunotherapy and chemotherapy, and regulating PANoptosis-related genes and proteins can promote cancer cell death and improve therapy outcomes, now the research on PANoptosis and cancer is just in its infancy ( 27 ). Given this, it is necessary to investigate the potential association between PANoptosis and cancers.…”
Section: Introductionmentioning
confidence: 99%